Pemahaman Konsep dan Hasil Belajar Mahasiswa Kimia Umum dalam Penerapan Model Pembelajaran Concept Attainment - Yusran Khery; Pahriah Pahriah (Lembaga Penelitian dan Pendidikan Mandala, 2016)
The aim of this research was to evaluate correlation student concept understanding and influence of concept attainment model of learning to their achievement on general chemistry learning. This was carried out in correlation and quasi experimental form of study. Subject is fisrt year FPMIPA IKIP Mataram student on academic year 2015/2016 who programming general chemistry lecture. There are 33 student split on to 20 and 13 successively on experiment and control group. Data was collected by concept understanding test and learning ecvievment test. Data was analyzed by correllation, regression, and mann whitney test pf statistic. Research result showed that (1) the higher student concept understanding the greater student learning achievement on general chemistry lecture by concept attainment model of learning. Value of rcount (0,969) higher than rtable (0.454) on degree of freedom = 19 and significant value 0.05. The influence of concept understanding to student learning achievement compatible with regression equation is y=1,194x – 1,353; (2) Concept attainment model of learning was influence student learning achievement. Nilai rata-rata hasil belajar mahasiswa kelas eksperimen (61,33) lebih tinggi daripada kelas control (35,9). Value of U1 (27) < Utable (α=0.05) (67) < U2 (233)